Reconstructing Islamic Historiography Post-Orientalism: A New Paradigm for Historical Knowledge Production in Global Islamic Studies - Hussein Al-Shuqairat; Abd Al-Razzak Mahmoud Al-Maani; Mohanad Nayef Aldajah; Shamshadin Kerim (Yayasan Albahriah Jamiah Indonesia, 2026)
The dominance of the orientalist paradigm in modern Islamic historiography has resulted in the construction of historical knowledge that tends to position Muslim societies as objects of representation through an external epistemological framework. Although post-orientalist critique has developed widely, studies that systematically explain the epistemological and methodological transformations of Islamic historiography within global knowledge production remain relatively limited. This study aims to analyze the process of reconstructing Islamic historiography post-orientalism and to formulate the characteristics of a new paradigm for the production of historical knowledge in global Islamic studies. The study uses a qualitative approach based on literature studies employing critical historiographical methods and epistemological analysis of the works of orientalists, postcolonial thinkers, and contemporary Islamic historiography, purposively selected for their relevance to the issue of historical knowledge production. The results show that the reconstruction of Islamic historiography proceeds through three main transformations. First, the deconstruction of essentialist, ahistorical, and Eurocentric assumptions that have shaped the narrative of Islamic history. Second, a methodological shift toward an interdisciplinary approach that integrates history, anthropology, sociology, area studies, and network analysis to explain the complexity of Muslim historical experiences. Third, the emergence of transnational historiography positions the Islamic world as a global space of interaction through the circulation of ideas, intellectual mobility, cultural exchange, and cross-regional political relations. This transformation has resulted in a historiographic paradigm that is more pluralistic, contextual, multi-perspective, and reflective of the diversity of sources and historical actors. In conclusion, post-orientalist Islamic historiography offers a new epistemological framework that strengthens the decolonization of knowledge and the development of a more inclusive global study of Islam.